Adaptation and evaluation of the willtry tool among children in Guam - Aflague, T.; Leon Guerrero, R.; Boushey, Carol (U.S. Centers for Disease Control and Prevention, National Center for Chronic Disease Prevention and Health Promotion, 2014)
Introduction: Fruit and vegetable consumption may reduce risk for chronic disease and obesity. Children's fruit and vegetable intake is mediated by a preference or willingness to try them. This study's primary objective was to adapt the previously validated WillTry tool and to evaluate the adapted version among children in Guam. Methods: Adaptations to the WillTry tool included both novel fruits and vegetables unique to Guam and common ones. Children aged 3 to 11 years who attended 2 community-based summer day camps in 2013 were shown images matching 14 food questions in an initial interview and in a second interview conducted 3 to 72 hours later. Responses were "no," "maybe," or "yes" and were coded as 1, 2, or 3, respectively. A higher score indicated more willingness to try fruits and vegetables. Factor analyses determined components of willingness. Psychometric properties and reliability were analyzed. Results: Sixty-five children completed the first interview, and 64 completed the second. Factor analyses revealed 3 components (scales):1) local novel (guava, breadfruit, eggplant, sweet sop, star apple, taro leaves), 2) local common (carrot, papaya, long beans, salad greens), and 3) imported (apple, canned peaches, canned corn). All but the imported scale had sufficient internal consistency (Cronbach's a > 0.69). Each scale had substantial reliability (ICC > 0.76). We found no significant differences by age, sex, or type of camp for any scale. Mean scores were 2.1 (local novel), 2.4 (local common), and 2.7 (imported), and all were significantly different. Conclusion: The adapted WillTry was culturally relevant and had psychometric properties similar to those of the original. An unexpected finding was the tool's potential for documenting the nutrition transition.